Patient-reported missed nursing care correlated with adverse events - Kalisch, Beatrice J; Xie, Boqin; Dabney, Beverly Waller (American journal of medical quality, 2014)
The aim of this study was to determine the extent and type of missed nursing care as reported by patients and the association with patient-reported adverse outcomes. A total of 729 inpatients on 20 units in 2 acute care hospitals were surveyed. The MISSCARE Survey-Patient was used to collect patient reports of missed care. Patients reported more missed nursing care in the domain of basic care (2.29 ± 1.06) than in communication (1.69 ± 0.71) and in time to respond (1.52 ± 0.64). The 5 most frequently reported elements of missed nursing care were the following: (a) mouth care (50.3%), (b) ambulation (41.3%), (c) getting out of bed into a chair (38.8%), (d) providing information about tests/procedures (27%), and (e) bathing (26.4%). Patients who reported skin breakdown/pressure ulcers, medication errors, new infections, IVs running dry, IVs infiltrating, and other problems during the current hospitalization reported significantly more overall missed nursing care.